Virus Particle Content of Smallpox Vaccines - Dunlap, R. C. (1970)
Calf lymph smallpox vaccines contain too much extraneous debris for an accurate assessment of their virus particle content. The process of partial purification of the vaccine utilizing enzymatic digestion by chymotrypsin, subtilisin, and collagenase solubilized enough debris to permit electron microscopic virus particle count. Enzyme treatment did not degrade or destroy the virus nor did it reduce the infective titer. Commercial vaccines studied ranged in virus content from 1.89 × 10(9) to 1.09 × 10(11) virus particles/ml. The pocking efficiencies on the chorioallantoic membrane of some of these vaccines varied from 200 to 1,200 virus particles per pock-forming unit.